Identifikasi peranan Silabus Pembelajaran dalam peningkatkan kualitas Pendidikan - Capah, Malindung (Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study is to identify the important role of the learning syllabus in improving the quality of education, including in terms of planning, evaluation, and adaptation to the development of the times. Qualitative methods are used to conduct an analysis of literature and educational practices related to the learning syllabus. These practices include educational standards, student progress evaluation, and learning planning. According to the study, the syllabus helps teachers organize learning systematically, improves the consistency of materials in the classroom, facilitates the evaluation of student progress, and provides flexibility to adapt to social and technological changes. The results show that creating a relevant and adaptable syllabus is a major step towards a successful education system. The syllabus must be continuously updated to meet the needs of the times and prepare students to face challenges around the world. Educators and education policy makers must commit to doing so.